THE RELATIONSHIP BETWEEN MARKETING MIX AND JBOUND VISITORS’ DECISION MAKING - Dina Hariani; Fadhil Hammadi (Sekolah Tinggi Pariwisata Mataram, 2021)
Educational tourism is a new trend that is in demand by several tourists, especially by families, educational institutions, and others. Jbound Bogor is an educational tourism and family recreation located in the city of Bogor, West Java, Indonesia. The Covid-19 pandemic that hit the world, including Indonesia, caused huge losses in the tourism sector. JBound is one of the tourist attractions affected by the pandemic, the policy for large-scale social restrictions carried out by the Indonesian government during the pandemic limited the number of tourist visitors and caused domestic tourists to postpone their traveling plans. Managers of tourist attractions must find strategies to market their products or services to consumers/tourists to survive in the midst of the coronavirus pandemic. Jbound Bogor reopened its tourist area in November 2020. One of the optimizations carried out by jbound is to maximize the marketing mix strategies including product, price, promotion, and place. This study uses a quantitative approach which is carried out through data collection at the object location using secondary data and primary data. This study aims to determine and explain the relationship or influence of product, price, promotion, and place on JBound visitor decision-making both partially and simultaneously. The sample analyzed was 100 respondents using non-probability sampling technique and purposive sampling method, namely tourists who have visited the Jbound Bogor. The research instrument used a questionnaire and was analyzed using multiple regression analysis. This research was conducted to determine which variables have an influence on decision-making. In this research, the independent variable used is product (X1), price (X2), promotion (X3), and place (X4) while the dependent variable is the visitors’ decision-making (Y). Based on the calculation of multiple linear regression analysis resulted in marketing mix has a significant influence both partially and simultaneously on visitor decision-making.